A New Z-axis Resonant Micro-Accelerometer Based on Electrostatic Stiffness - Bo Yang; Xingjun Wang; Bo Dai; Xiaojun Liu (Sensors, 2015)
Presented in the paper is the design, the simulation, the fabrication and the experiment of a new z-axis resonant accelerometer based on the electrostatic stiffness. The new z-axis resonant micro-accelerometer, which consists of a torsional accelerometer and two plane resonators, decouples the sensing movement of the accelerometer from the oscillation of the plane resonators by electrostatic stiffness, which will improve the performance. The new structure and the sensitive theory of the acceleration are illuminated, and the equation of the scale factor is deduced under ideal conditions firstly. The Ansys simulation is implemented to verify the basic principle of the torsional accelerometer and the plane resonator individually. The structure simulation results prove that the effective frequency of the torsional accelerometer and the plane resonator are 0.66 kHz and 13.3 kHz, respectively. Then, the new structure is fabricated by the standard three-mask deep dry silicon on glass (DDSOG) process and encapsulated by parallel seam welding. Finally, the detecting and control circuits are designed to achieve the closed-loop self-oscillation, to trace the natural frequency of resonator and to measure the system frequency. Experimental results show that the new z-axis resonant accelerometer has a scale factor of 31.65 Hz/g, a bias stability of 727 µg and a dynamic range of over 10 g, which proves that the new z-axis resonant micro-accelerometer is practicable.